Prevalence of intradialytic hypotension, clinical symptoms and nursing interventions - a three-months, prospective study of 3818 haemodialysis sessions. Issue 1 (December 2016) - Kuipers, Johanna; Oosterhuis, Jurjen; Krijnen, Wim; Dasselaar, Judith; Gaillard, Carlo; Westerhuis, Ralf; Franssen, Casper
Abstract Background Intradialytic hypotension (IDH) is considered one of the most frequent complications of haemodialysis with an estimated prevalence of 20–50 %, but studies investigating its exact prevalence are scarce. A complicating factor is that several definitions of IDH are used. The goal of this study was, to assess the prevalence of IDH, primarily in reference to the European Best Practice Guideline (EBPG) on haemodynamic instability: A decrease in systolic blood pressure (SBP) ≥20 mmHg or in mean arterial pressure (MAP) ≥10 mmHg associated with a clinical event and the need for nursing intervention. Methods During 3 months we prospectively collected haemodynamic data, clinical events, and nursing interventions of 3818 haemodialysis sessions from 124 prevalent patients who dialyzed with constant ultrafiltration rate and dialysate conductivity. Patients were considered as having frequent IDH if it occurred in >20 % of dialysis sessions. Results Decreases in SBP ≥20 mmHg or MAP ≥10 mmHg occurred in 77.7 %, clinical symptoms occurred in 21.4 %, and nursing interventions were performed in 8.5 % of dialysis sessions. Dialysis hypotension according to the full EBPG definition occurred in only 6.7 % of dialysis sessions. Eight percent of patients had frequent IDH. Conclusions The prevalence of IDH according to the EBPG definition is low. The dominant determinant of the EBPG definition was nursing intervention since this was the component with the lowest prevalence. IDH seems to be less common than indicated in the literature but a proper comparison with previous studies is complicated by the lack of a uniform definition.